Mesenchymal MACF1 Facilitates SMAD7 Nuclear Translocation to Drive Bone Formation - Fan Zhao; Xiaoli Ma; Wuxia Qiu; Pai Wang; Ru Zhang; Zhihao Chen; Peihong Su; Yan Zhang; Dijie Li; Jianhua Ma; Chaofei Yang; Lei Chen; et al. (Cells, 2020)
Microtubule actin crosslinking factor 1 (MACF1) is a large crosslinker that contributes to cell integrity and cell differentiation. Recent studies show that MACF1 is involved in multiple cellular functions such as neuron development and epidermal migration, and is the molecular basis for many degenerative diseases. MACF1 is highly abundant in bones, especially in mesenchymal stem cells; however, its regulatory role is still less understood in bone formation and degenerative bone diseases. In this study, we found MACF1 expression in mesenchymal stem cells (MSCs) of osteoporotic bone specimens was significantly lower. By conditional gene targeting to delete the mesenchymal Macf1 gene in mice, we observed in MSCs decreased osteogenic differentiation capability. During early stage bone development, the MACF1 conditional knockout (cKO) mice exhibit significant ossification retardation in skull and hindlimb, and by adulthood, mesenchymal loss of MACF1 attenuated bone mass, bone microarchitecture, and bone formation capability significantly. Further, we showed that MACF1 interacts directly with SMAD family member 7 (SMAD7) and facilitates SMAD7 nuclear translocation to initiate downstream osteogenic pathways. Hopefully these findings will expand the biological scope of the MACF1 gene, and provide an experimental basis for targeting MACF1 in degenerative bone diseases such as osteoporosis.